# The PDF of minimum of two random varible. [closed]

Let $X$ and $Y$ be two random variables with respective PDFs $P_X(x)$ and $P_Y(y)$ given by

\begin{align}\label{Eq_Ap_2} P_{X}(x)&=M\beta e^{-\beta x}\begin{pmatrix} 1-e^{-\beta x} \end{pmatrix}^{M-1}\\ &=M\beta \sum_{m=0}^{N-1}(-1)^n\binom{M-1}{m}\begin{pmatrix} e^{-\beta x} \end{pmatrix}^{m+1} \end{align}

\begin{align} P_{Y}(y)&=N\beta e^{-\beta y}\begin{pmatrix} 1-e^{-\beta y} \end{pmatrix}^{N-1}\\ &=N\beta \sum_{n=0}^{N-1}(-1)^n\binom{N-1}{n}\begin{pmatrix} e^{-\beta y} \end{pmatrix}^{n+1}.\label{Eq_Ap_3} \end{align}

What is the PDF of $$Z=\min\{X,Y\}$$

## closed as off-topic by owen88, Did, Dando18, Isaac Browne, JonMark PerryApr 29 '18 at 5:10

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – owen88, Did, Dando18, Isaac Browne, JonMark Perry
If this question can be reworded to fit the rules in the help center, please edit the question.

The independence between $X$ and $Y$ will be assumed, otherwise there's no way to proceed.

TL;DR : see Eq.\eqref{Eq05} for the end result and an intuitive interpretation that follows.

Note that $X$ can be viewed as the maximum of $M$ exponential random variables that are i.i.d. with rate of $\beta$. Denote this set as $U_i$ for $i = 1$ to $M$. All $U_i$ have the same density $f_U(t) = \beta\, \mathrm{Exp}(-\beta t)$.

Similarly, $Y$ has the same distribution as the maximum of another set of $N$ exponential i.i.d with rate $\beta$. Call these $W_k$ for $k = 1$ to $N$, and their common density is the same $f_W(t) = \beta\, \mathrm{Exp}(-\beta t)$.

The two sets $U_i$ and $W_k$ are independent, otherwise $X$ and $Y$ cannot be independent.

Denote the cumulative function as $F_X(t) \equiv \Pr\{ X < t\}$, not to be confused with the density $P_X(x)$. The same notation goes for $F_U(t)$, $F_W(t)$, and $F_Y(t)$. We are given \begin{align*} F_X(t) &= \bigl( F_U(t) \bigr)^M = \left( 1 - e^{-\beta t} \right)^M & &\text{and} & F_Y(t) &= \bigl( F_W(t) \bigr)^N = \left( 1 - e^{-\beta t} \right)^N \end{align*}

There is actually an intuitive shortcut to obtain the density of $Z = \min\{X, Y\}$, as is often the case with order statistics. Nonetheless, let's do it concretely from the cumulative function to appreciate some inner structure.

\begin{align*} F_Z(t) \equiv \Pr\{ Z < t\} &= \Pr\{ X~\text{is smaller} \} + \Pr\{ Y~\text{is smaller} \} \\ &= \color{blue}{ \Pr\{ X < t ~~\&~~ Y> X \}} + \Pr\{ Y < t ~~\&~~ X > Y \} \\ &= \color{blue}{ \int_{x = 0}^t \int_{y=x}^{\infty} P_X(x) P_Y(y)\,\mathrm{d}y \,\mathrm{d}x } + \int_{y = 0}^t \int_{x=y}^{\infty} P_X(x) P_Y(y)\,\mathrm{d}x \,\mathrm{d}y \tag{1} \label{Eq01} \end{align*} In the above the fact is already invoked that $X \perp Y \implies P_{XY}(x,y) = P_X(x)P_Y(y)$

Consider the first integral in Eq.\eqref{Eq01}, which is the region above the diagonal in the $X$-$Y$ plane. \begin{align*} \color{blue}{ \Pr\{ X < t ~~\&~~ Y> X \} } &= \int_{x = 0}^t \left[ P_X(x)\int_{y=x}^{\infty} P_Y(y)\,\mathrm{d}y \right] \,\mathrm{d}x \\ &= \int_{x = 0}^t \Bigl[ P_X(x) \bigl( 1 - F_Y(x) \bigr)\Bigr] \,\mathrm{d}x \\ &= \int_{x = 0}^t P_X(x) \cdot 1 \,\mathrm{d}x - \int_{x = 0}^t P_X(x) \cdot F_Y(x) \,\mathrm{d}x \\ &= F_X(t) - \int_{x = 0}^t M \beta e^{-\beta x} \left( 1 - e^{-\beta x} \right)^M \cdot \left( 1 - e^{-\beta x} \right)^N \,\mathrm{d}x \end{align*} Since in the end we will take the derivative with respect to $t$ to obtain the density as in $$P_Z(t) = \frac{ \mathrm{d}F_Z(t) }{ \mathrm{d} t} = \color{blue}{ \frac{ \mathrm{d}\Pr\{ X < t ~~\&~~ Y> X \} }{ \mathrm{d} t} } + \frac{ \mathrm{d}\Pr\{ Y < t ~~\&~~ X > Y \} }{ \mathrm{d} t} \tag{2} \label{Eq02}$$ we might as well do it now for the above-diagonal piece. $$\color{blue}{ \frac{ \mathrm{d}\Pr\{ X < t ~~\&~~ Y> X \} }{ \mathrm{d} t}} = P_X(t) - \color{magenta}{\frac{ M }{ M+N } } (M+N) \beta e^{-\beta t} \left( 1 - e^{-\beta t} \right)^{M+N} \tag{3} \label{Eq03}$$ After the leading $P_X(t)$ we get the $\color{magenta}{\text{scaled}}$ version of the density of the maximum of $(M+N)$ exponential i.i.d. with rate $\beta$.

Similarly, that the second piece of integral in Eq.\eqref{Eq01} for the below-diagonal region will give: $$\frac{ \mathrm{d}\Pr\{ Y < t ~~\&~~ X> Y \} }{ \mathrm{d} t} = P_Y(t) - \color{magenta}{\frac{ N }{ M+N } } (M+N) \beta e^{-\beta t} \left( 1 - e^{-\beta t} \right)^{M+N} \tag{4} \label{Eq04}$$

Put Eq.\eqref{Eq03} and Eq.\eqref{Eq04} them together according to Eq.\eqref{Eq02} we get a full piece. $$P_Z(t) = P_X(t) + P_Y(t) - P_T(t) \quad \text{where} \quad P_T(t) = (M+N) \beta e^{-\beta t} \left( 1 - e^{-\beta t} \right)^{M+N} \tag{5} \label{Eq05}$$

That is, the density of $Z = \min\{X,Y\}$ is the sum of the densities of $X$ and $Y$ minus the density of $T$, where $T$ is the maximum of $(M+N)$ exponential i.i.d. with rate $\beta$

There's actually a heuristic argument for this "sum then minus" of densities. Note that here we have only two things $X$ and $Y$, therefore $$X + Y = \min\{X, Y\} + \max\{X, Y\}$$ Many nice properties come out of this fact, and there are some nice example for the discrete distribution as well. In particular, consider the infinitesimal probability mass between (the dummy) $t$ to $t+ \mathrm{d}t$. With notations $Z = \min\{X, Y\}$ and $T = \max\{X, Y\}$, we have $$\Pr\{ t < X < t+ \mathrm{d}t \} + \Pr\{ t < Y < t+ \mathrm{d}t \} = \Pr\{ t < Z < t+ \mathrm{d}t \} + \Pr\{ t < T < t+ \mathrm{d}t \} \tag{6} \label{Eq06}$$ Intuitively, the tiny probability mass is proportional to the density as in $$\Pr\{ t < X < t+ \mathrm{d}t \} = P_X(t)\mathrm{d}t \tag*{, similar for Y, Z, and T.}$$ Therefore, Eq.\eqref{Eq06} becomes an equation of the densities. $$P_X(t) + P_Y(t) = P_Z(t) + P_T(t) \\ P_Z(t) = P_X(t) + P_Y(t) - P_T(t)$$ This can be considered an explanation for Eq.\eqref{Eq05} as well as an intuitive shortcut to derive it.

You did not state it, but I assume X, Y are independent

Firstly find the CDF of $Z = \min(X,Y)$ and then differentiate it w.r.t. z to get its PDF: $\mathbb{P}(Z \leq z) = 1- \mathbb{P}(\min(X,Y) > z) = 1 - \mathbb{P}(X > z)\mathbb{P}(Y > z) = 1 - (1 - \mathbb{P}(X \leq z))(1 - \mathbb{P}(Y \leq z)) = \mathbb{P}(Y \leq z) + \mathbb{P}(X \leq z) - \mathbb{P}(Y \leq z)\mathbb{P}(X \leq z)$

Taking the derivative w.r.t. z yields: $P_Z(z) = P_Y(z) + P_X(z) - P_Y(z)\mathbb{P}(X \leq z) - \mathbb{P}(Y \leq z)P_X(z) = P_X(z)\mathbb{P}(Y \geq z) + P_Y(z)\mathbb{P}(X \geq z) = P_X(z)\int_z^{\infty}P_Y(t)dt + P_Y(z)\int_z^{\infty}P_X(t)dt$

Substituting your PDFs and computing the integrals yields the final formula. Since the sum is finite you can interchange the integration and summation. Computing the integrals is not hard.

• hi @Mateusz Eggink what is mean $\int_{z}^{\infty}P_Y(t)dt$ dose it mean $CDF_Y(\infty)-CDF_Y(z)$ – Mokhtar Apr 28 '18 at 21:04
• If you want to express $\int_z^{\infty}P_Y(t)dt$ using the CDF of Y then what you have written is correct. However, remember that $CDF_Y(\infty) = 1$. Here I specifically expressed the probability $\mathbb{P}(Y \geq z)$ using the PDF of Y because the CDF is not given in the exercise. – Mateusz Eggink Apr 28 '18 at 21:14
• ok we can say $CDF_Y(z)=1-P(Y\geq z)$ and thank you – Mokhtar Apr 28 '18 at 21:54

Assume X and Y are independent. $P(Z\gt z)=P(X\gt z)P(Y\gt z)$. Thus $P(Z\lt z)=1-(1-P(X\lt z))(1-P(Y\lt z))=P(X\lt z)+P(Y\lt z)-P(X\lt z)P(Y\lt z).$

Therefore $P_Z(z)=P_X(z)+P_Y(z)-(CDF_X(z)P_Y(z)+CDF_Y(z)P_X(z))$.

Note to comment - I was subconsciously using the formula for max rather than min before.

• This is partially incorrect. You can see the answer by @MateuszEggink (as it currently is) for a comparison. – Lee David Chung Lin Apr 28 '18 at 17:35